2015
DOI: 10.1007/s11701-015-0514-3
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic surgery for mid or low rectal cancer in male patients after neoadjuvant chemoradiation therapy: comparison of short-term outcomes

Abstract: The aim of our study was to compare short-term outcomes of robotic and laparoscopic sphincter-saving total mesorectal excision (TME) in male patients with mid-low rectal cancer (RC) after neadjuvant chemoradiotherapy (NCRT). The study was conducted as a retrospective review of a prospectively maintained database, and we analyzed 14 robotic and 65 laparoscopic sphincter saving TME (R-TME and L-TME, respectively) performed by one surgeon between 2005 and 2013. Patient characteristics, perioperative recovery, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 37 publications
6
39
2
Order By: Relevance
“…Sixteen studies [1013,1519,23–29] reported operative time. In particular, 1 study [28] indicated a shorter operative time with RTME, 3 studies [10,24,26] showed no significant difference between techniques, and the rest of studies suggested that operative time was longer with RTME than LTME.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen studies [1013,1519,23–29] reported operative time. In particular, 1 study [28] indicated a shorter operative time with RTME, 3 studies [10,24,26] showed no significant difference between techniques, and the rest of studies suggested that operative time was longer with RTME than LTME.…”
Section: Resultsmentioning
confidence: 99%
“…[1013,1519,23–29] Two studies [10,28] showed that it was shorter for RTME, 1 study [18] reported that it was a little longer for RTME, and the remaining studies indicated no significant difference between techniques. Pooled data analysis showed that there was no significant difference between the techniques [WMD = −0.69, 95% CI (−1.48 to 0.10); P  = .089], with high heterogeneity (I 2  = 81.8%; P  < .001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations